Expert System Application for Identification of Chili Plant Diseases Using Forward Chaining and Oreste Methods - Muthmainnah; Rizky Putra Fhonna; Safwandi; Veri Ilhadi (Sean Institute, 2021)
Chili is a plant that has an important role in human life. Apart from being a source of vitamins, chili can also be used as a mixture of food and medicine. In the implementation of planting, chili plantings often fail, including crop failure due to various kinds of diseases. However, to find out the type of disease that attacks it requires an expert / agricultural expert, while in handling chili plant diseases it is often time-constrained due to the limited knowledge of the farmers and the lack of an expert who is an expert in this field who can go directly to farmers. Therefore, to overcome the problems of farmers, a system that has knowledge like an expert in this case has knowledge of the symptoms and diseases of chili plants. To answer this problem, a web-based expert system application will be built. The design of this system uses the forward chaining and oreste method which is intended to assist farmers in diagnosing chili plant diseases. Expert systems are used in all fields, one of which is in the field of food crops. One of the benefits of expert systems in the field of food crops is that it makes it easier for farmers to detect diseases in chili plants so that farmers can find out the type of disease and how to handle it quickly without having to wait for experts who have competence in that field.